Addressing Current Criticism Regarding the Value of Self-Report Dietary Data. Issue 12 (14th October 2015) - Subar, Amy F; Freedman, Laurence S; Tooze, Janet A; Kirkpatrick, Sharon I; Boushey, Carol; Neuhouser, Marian L; Thompson, Frances E; Potischman, Nancy; Guenther, Patricia M; Tarasuk, Valerie; Reedy, Jill; Krebs-Smith, Susan M
Abstract: Recent reports have asserted that, because of energy underreporting, dietary self-report data suffer from measurement error so great that findings that rely on them are of no value. This commentary considers the amassed evidence that shows that self-report dietary intake data can successfully be used to inform dietary guidance and public health policy. Topics discussed include what is known and what can be done about the measurement error inherent in data collected by using self-report dietary assessment instruments and the extent and magnitude of underreporting energy compared with other nutrients and food groups. Also discussed is the overall impact of energy underreporting on dietary surveillance and nutritional epidemiology. In conclusion, 7 specific recommendations for collecting, analyzing, and interpreting self-report dietary data are provided: 1 ) continue to collect self-report dietary intake data because they contain valuable, rich, and critical information about foods and beverages consumed by populations that can be used to inform nutrition policy and assess diet-disease associations; 2 ) do not use self-reported energy intake as a measure of true energy intake; 3 ) do use self-reported energy intake for energy adjustment of other self-reported dietary constituents to improve risk estimation in studies of diet-health associations; 4 ) acknowledge the limitations of self-report dietary data and analyze and interpret them appropriately; 5 ) design studies and conduct analyses that allow adjustment for measurement error; 6 ) design new epidemiologic studies to collect dietary data from both short-term (recalls or food records) and long-term (food-frequency questionnaires) instruments on the entire study population to allow for maximizing the strengths of each instrument; and 7 ) continue to develop, evaluate, and further expand methods of dietary assessment, including dietary biomarkers and methods using new technologies.